2022
DOI: 10.1002/cctc.202200950
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Conversion of Glycerol to Acetol and Acrolein Using Metal Oxides: Surface Reactions, Prospects and Challenges

Abstract: Glycerol dehydration to acetol and acrolein is an interesting reaction pathway for conversion of biomass‐derived products. However, they undergo extensive deactivation due to coke deposition and sintering, requiring the design of stable catalysts. The oxides stand out due to their natural abundance, simple synthesis, low cost and tunable acidic, basic and redox properties. The different studies apply these oxides as pure phase, supported, mixed or doped. However, it is observed that despite the large number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 180 publications
1
6
0
Order By: Relevance
“…In the open literature, catalytic materials having redox sites, such as copper oxide, have been applied for the dehydration reaction of glycerol. 59,60 These results further verify the results obtained in CH 3 OH-TPSR experiments according to which the ratio of the acid/redox sites is significantly lower in the reduced catalyst compared to the fresh one. Performance data suggest that the reduced catalyst with the low acid/redox ratio promotes the complete deoxygenation to propylene while samples with higher ratios lead to partially deoxygenated products in agreement with the work of M. El Doukkali et al 40 Summarizing, catalyst hydrogen pre-treatment step is of utmost importance to obtaining the active sites for the reaction to proceed towards propylene production.…”
Section: Catalyst Reusabilitysupporting
confidence: 84%
See 1 more Smart Citation
“…In the open literature, catalytic materials having redox sites, such as copper oxide, have been applied for the dehydration reaction of glycerol. 59,60 These results further verify the results obtained in CH 3 OH-TPSR experiments according to which the ratio of the acid/redox sites is significantly lower in the reduced catalyst compared to the fresh one. Performance data suggest that the reduced catalyst with the low acid/redox ratio promotes the complete deoxygenation to propylene while samples with higher ratios lead to partially deoxygenated products in agreement with the work of M. El Doukkali et al 40 Summarizing, catalyst hydrogen pre-treatment step is of utmost importance to obtaining the active sites for the reaction to proceed towards propylene production.…”
Section: Catalyst Reusabilitysupporting
confidence: 84%
“…Thus, as the formation of both is highly favored, it can be assumed that both Lewis and Brønsted active sites co-exist on the catalyst surface which favor almost exclusively the formation of dehydration products. 58,59 Even though the production of both hydroxyacetone and acrolein require the presence of acid sites, their production from redox and/or basic sites is also feasible. In the open literature, catalytic materials having redox sites, such as copper oxide, have been applied for the dehydration reaction of glycerol.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that increasing the copper oxide dispersion can develop the catalyst acidity and activity for dehydrate glycerol selectively to acetol [ 30 , 31 ]. Generally, the greater acidity the catalyst possesses, the better catalytic performance it exhibits [ 1 , 7 ]. Therefore, it is reasonable to think that the presence of Y 2 O 3 facilitates the Cu dispersion, enhances the acidity, and thus promotes the selectivity for acetol production from glycerol.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last few decades, determining how to valorize glycerol has been widely investigating since the steep increasing biodiesel production results in an excess supply of glycerol [ 1 ]. Glycerol is a highly reactive molecule as it possesses three hydroxyl functional groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation